Determinant Factors Related To The Incidence Of Dysmenorrhea In Students Of Smk Al-Bana, Bogor Regency - hamidah, endah arwa; Prastia, Tika Noor; Tanrikulu, Lokman (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
Dysmenorrhea is pain in the lower abdomen, which can radiate to the lower back and legs. This study aims to analyze the picture and relationship between stress levels, physical activity, sleep quality, and menstrual cycles with the incidence of dysmenorrhea in Al Bana Vocational School students. The type of research method used is quantitative research with a Cross-sectional approach. The total population in this study was 108 respondents and an active sample of 69 respondents was obtained with a random sampling technique. The instrument in the study used was a questionnaire with direct distribution. The data analysis used was univariate analysis and bivariate analysis (chi-square). The results showed that there was a relationship between stress level (p-value = 0.006), sleep quality (p-value = 0.000), menstrual cycle (p-value = 0.000) and the incidence of dysmenorrhea, while there was no relationship between physical activity (p-value = 0.791) and the incidence of dysmenorrhea. The conclusion showed that there was a relationship between stress levels, sleep quality, menstrual cycles and the incidence of dysmenorrhea in Al Bana Vocational School students. For future researchers, it is recommended to conduct further research to analyze the incidence of dysmenorrhea by paying attention to other variables related to the incidence of dysmenorrhea.